2013
DOI: 10.1186/2051-5960-1-47
|View full text |Cite
|
Sign up to set email alerts
|

Disorganization of neocortical lamination in focal cortical dysplasia is brain-region dependent: evidence from layer-specific marker expression

Abstract: BackgroundFocal cortical dysplasias (FCD) are local disturbances of neocortical architecture and a common cause of pharmaco-resistant focal epilepsy. Little is known about the pathomechanisms leading to architectural abnormalities associated with FCD.ResultsIn the present study we compared 52 FCD cases originating from the frontal or temporal lobe with or without Ammon’s horn sclerosis (AHS) with regard to structural and molecular differences. We applied layer-specific (ER81, RORß, SMI32, TLE4) and interneuron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
25
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(35 citation statements)
references
References 47 publications
8
25
2
Order By: Relevance
“…We find that both upper cortical layers and lower cortical layers are normal in terms of neuronal identity and position based on distribution of Cux1 positive neurons (Figure 4A), CTIP-2 neurons (Figure 4A), and Brn2 neurons (data not shown). Although we were not able to immunostain for specific neuronal layers in human tissue, the epileptogenic tissue from FCD cases in our study have abnormal neuronal density and distribution consistent with known defects (Fauser et al, 2013; Thom et al, 2005) (Figure 4B). Thus, Emx-Cre; Clock flox/flox mice do not phenocopy the laminar defects seen in FCD cases.…”
Section: Resultsmentioning
confidence: 64%
See 1 more Smart Citation
“…We find that both upper cortical layers and lower cortical layers are normal in terms of neuronal identity and position based on distribution of Cux1 positive neurons (Figure 4A), CTIP-2 neurons (Figure 4A), and Brn2 neurons (data not shown). Although we were not able to immunostain for specific neuronal layers in human tissue, the epileptogenic tissue from FCD cases in our study have abnormal neuronal density and distribution consistent with known defects (Fauser et al, 2013; Thom et al, 2005) (Figure 4B). Thus, Emx-Cre; Clock flox/flox mice do not phenocopy the laminar defects seen in FCD cases.…”
Section: Resultsmentioning
confidence: 64%
“…Disruption of the layered structure or lamination of cortical neurons is common in both FCD (Fauser et al, 2013; Thom et al, 2005) and TSC (Muhlebner et al, 2016). Because CLOCK is expressed in embryonic stages when neurons are migrating (Figure S2I), and the conditional deletion of the Clock gene also occurs during embryonic stages, we first determined whether the position of cortical neurons is normal in Emx-Cre; Clock flox/flox mice.…”
Section: Resultsmentioning
confidence: 99%
“…Immunohistochemical single-labeling using peroxidase-antiperoxidase (PAP) procedures described previously (Meade et al, 2002; Reiner et al, 2012a) was employed to visualize a variety of neurochemical features in mutant and control brains. To study the laminar organization of cerebral cortex, we used immunolabeling with a mouse monoclonal antibody (Sigma-Aldrich, C89848) to detect the lightly labeled calbindinergic neurons defining layers 2–3 (Van Brederode et al, 1991; Kondo et al, 1997; Fauser et al, 2013), a rabbit polyclonal antibody (Sigma/Aldrich, V2514) to detect VGLUT2+ fibers in layer 4 (Deng et al, 2013), the SMI-32 mouse monoclonal antibody (Covance, SMI-32R) and a rat monoclonal antibody against Ctip2 (Abcam, AB18465) to define neurons in layer 5 (Özdinler et al, 2011; Fauser et al, 2013), and a rabbit polyclonal antibody against FoxP2 (Abcam, AB16046) to define neurons in layer 6 (Özdinler et al, 2011). The specificity of these antibodies for their target antigens has been demonstrated by the manufacturer by Western blot and in published studies (Stillman et al, 2009; Hirano et al, 2011; Hashimoto et al, 2012; Huang et al, 2012; Lei et al, 2013).…”
Section: Methodsmentioning
confidence: 99%
“…Using layer-specific markers, studies found abnormal laminar expression patterns in CD [64] and also that disruption of cortical lamination is brain region dependent, most prominent in frontal CD and in layers III and VI [65]. In addition, layer-specific gene expression in CD type II cases revealed that normal-appearing pyramidal neurons are better organized in different laminae than dysmorphic neurons and balloon cells, which show more altered migratory patterns [66].…”
Section: Architectural and Cellular Abnormalities In CDmentioning
confidence: 99%